Implementation of fuzzy logic control for the automation of diesel engine cooling systems - Randis Randis; Sri Susilawati Islam; Nur yanti; Novita Novita (Politeknik Negeri Lhokseumawe, 2023)
Conventional cooling systems on four-wheeled vehicles generally use a cooling fan driven by the crankshaft through pulleys and a belt (V-belt), causing the wastage of fuel in the vehicle. This study aims to design and implement fuzzy logic control on a prototype of an automatic cooling system for a diesel engine. The tool's design uses the experimental method, uses Arduino as a microcontroller that functions as a data processing center, with inputs of two temperature sensors and a DC motor as output to rotate the fan, and fuzzy logic control methods as an automatic control system. The research results show that this tool can operate automatically according to the engine temperature, so it is expected to produce greater effectiveness and efficiency. Measurements on each component have been carried out and show satisfactory results, testing on the temperature sensor shows a small error. Comprehensive testing of the tool shows good performance, including the PWM output to adjust the rotational speed of the fan motor so that the system can be used properly. This research will help create a prototype of an automatic cooling system for a diesel engine cooling system so that it can be developed to reveal better fuel efficiency in the future.